2020
DOI: 10.3389/fnmol.2020.00157
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Endurance Associated With Moderate Exercise in Rats Induces Cerebellar Oxidative Stress and Impairs Reactive GFAP Isoform Profile

Abstract: Ultra-endurance (UE) race has been associated with brain metabolic changes, but it is still unknown which regions are vulnerable. This study investigated whether high-volume training in rodents, even under moderate intensity, can induce cerebellar oxidative and inflammatory status. Forty-five adult rats were divided into six groups according to a training period, followed or not by an exhaustion test (ET) that simulated UE: control (C), control + ET (C-ET), moderate-volume (MV) training and MV-ET, high-volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…On the other hand, interestingly, competitions over 360 km began to become common in 2017, a fact that should be further explored. In part, it can be explained by the increase in psychological resilience [9]. 4.2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, interestingly, competitions over 360 km began to become common in 2017, a fact that should be further explored. In part, it can be explained by the increase in psychological resilience [9]. 4.2.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently, the participation in challenges over 180 km is advancing. These competitions are considered extreme events exceeding 1000 km, making them a superior challenge, which presents the athletes with a series of adversities (i.e., extreme weather conditions and nutritional care) [ 9 ]. Thus, an understanding of the profile of athletes is important to guide their training and preparation for long-term performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the increase in free radicals, there is an indication that the antioxidant activity in the body tends not to decrease after intense chronic and acute exercises [46]. De Souza et al, [49] demonstrated lipid peroxidation in high intensity and long duration exercises in healthy individuals. Plasma MDA levels were measured before and after exercise until fatigue and did not undergo any significant changes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, long-term treadmill exercise reduced the number of hippocampal GFAP+ astrocytes in APP/PS1 mice model of AD, and voluntary running decreased the intensity and size of activated astrocytes in the cortex and hippocampus in the double transgenic APPswe/PS1ΔE9 mouse model of AD [ 89 , 90 ]. Moreover, ultra-endurance race simulation after high-volume training in rodents altered the GFAP isoform profile, suggesting impaired astrocyte reactivity in the cerebellum [ 91 ], where, in normal conditions, astrocytes regulate the homeostasis of this region, locomotor performance, and represent an antioxidant resource [ 92 ]. A combination of treadmill and running wheel for 4 weeks significantly increased the extent of astrocyte processes in adult mice.…”
Section: The Effects Of Physical Exercise On Astrocytesmentioning
confidence: 99%